2014
DOI: 10.2337/dc14-1514
|View full text |Cite|
|
Sign up to set email alerts
|

Six-Week Versus Twelve-Week Antibiotic Therapy for Nonsurgically Treated Diabetic Foot Osteomyelitis: A Multicenter Open-Label Controlled Randomized Study

Abstract: OBJECTIVELittle is known about the optimal duration of antibiotic therapy for diabetic foot osteomyelitis (DFO). This study sought to compare the effectiveness of 6 versus 12 weeks of antibiotic therapy in patients with DFO treated nonsurgically (i.e., antibiotics alone). RESEARCH DESIGN AND METHODSThis was a prospective randomized trial comparing 6-versus 12-week duration of antibiotic treatment. Remission of osteomyelitis during the monitoring period was defined as complete and persistent (>4 weeks) healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
179
2
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(198 citation statements)
references
References 27 publications
3
179
2
14
Order By: Relevance
“…The study suggests that WBC-SPECT/CT predicts remission after a 6 or 12 week course of antibiotic treatment, and found that the overall remission rate was higher than most of the rates observed in the literature [4][5][6][7][8][9][10][11][12][13][14]. As is generally observed in studies dealing with DFO, the overwhelming majority of the population included in the present study had neuropathy and there was a high rate of chronic complications associated with long-term diabetes.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…The study suggests that WBC-SPECT/CT predicts remission after a 6 or 12 week course of antibiotic treatment, and found that the overall remission rate was higher than most of the rates observed in the literature [4][5][6][7][8][9][10][11][12][13][14]. As is generally observed in studies dealing with DFO, the overwhelming majority of the population included in the present study had neuropathy and there was a high rate of chronic complications associated with long-term diabetes.…”
Section: Discussioncontrasting
confidence: 43%
“…Individuals with peripheral arteriopathy or renal insufficiency were not excluded in the absence of an indication for bone resection or amputation. As in recent randomised controlled studies on DFO [13,14], at least 40 participants were included, with a minimum of 20 participants treated for 6 weeks and 20 participants treated for 12 weeks, with an expected rate of DFO remission above 70%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While possible, this indirect benefit remains to be established and even if it is, the limited availability of SPECT/CT will remain a barrier -at least in the short term. More trials are urgently needed to extend the important finding of Tone and colleagues that a 6 week course of antibiotics was not inferior to a longer one [11] and, in particular, to determine whether antibiotic courses of just 2 or 3 weeks may be as effective in the management of osteomyelitis as they can be in the management of soft tissue infection.…”
Section: Spect/ct Scanningmentioning
confidence: 99%